2013
DOI: 10.1111/iwj.12026
|View full text |Cite
|
Sign up to set email alerts
|

A prospective window into medical device‐related pressure ulcers in intensive care

Abstract: The aim of this study was to determine the prevalence, severity, location, aetiology, treatment and healing of medical device-related pressure ulcers (PUs) in intensive care patients for up to 7 days. A prospective repeated measures study design was used. Patients in six intensive care units of two major medical centres, one each in Australia and the USA, were screened 1 day per month for 6 months. Those with device-related ulcers were followed daily for up to 7 days. The outcome measures were device-related u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
11
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(171 citation statements)
references
References 14 publications
(24 reference statements)
10
134
11
16
Order By: Relevance
“…Their results showed a 3.1% prevalence of medical devicerelated injuries (15/483) with 6.1% (8/132) in the Australian sample and 2.0% (7/351) in the US sample. 37 The incidence of medical device-related injuries was higher in our study (control group, 39 injuries in 31 patients); however, our study was conducted before the Coyer comparative audit control group for 28% of days observed (P < .001). There was no difference between groups in frequency of bed baths (intervention group, 1.49 bed baths/day; control group, 1.46 bed baths/day) or the application of moisturizer to dry skin (11.7% of days for both the intervention group and the control group).…”
Section: 8contrasting
confidence: 53%
See 1 more Smart Citation
“…Their results showed a 3.1% prevalence of medical devicerelated injuries (15/483) with 6.1% (8/132) in the Australian sample and 2.0% (7/351) in the US sample. 37 The incidence of medical device-related injuries was higher in our study (control group, 39 injuries in 31 patients); however, our study was conducted before the Coyer comparative audit control group for 28% of days observed (P < .001). There was no difference between groups in frequency of bed baths (intervention group, 1.49 bed baths/day; control group, 1.46 bed baths/day) or the application of moisturizer to dry skin (11.7% of days for both the intervention group and the control group).…”
Section: 8contrasting
confidence: 53%
“…This study is the first to report a successful intervention to reduce medical devicerelated injuries, an underreported phenomenon. Coyer and colleagues 37 recently conducted a comparative audit of medical device-related injuries in critically ill patients in ICUs in Australia and the United States. Their results showed a 3.1% prevalence of medical devicerelated injuries (15/483) with 6.1% (8/132) in the Australian sample and 2.0% (7/351) in the US sample.…”
Section: 8mentioning
confidence: 99%
“…This risk is higher among critically ill patients because this group of patients requires more medical devices for monitoring and therapeutic purposes (4,7). Coyer et al reported that the prevalence of medical devicerelated pressure ulcer was 3·1% in ICU patients (8). The present case shows that skin may be affected by cervical collar, and as a result pressure ulcer may develop.…”
Section: Dear Editorsmentioning
confidence: 49%
“…51,53,54,56,57 It has been suggested that the prevalence of these ulcers may be underestimated because systematic evaluation for device-related PU recurrence is not part of a routine skin assessment. 58 While PUs cause pain and suffering, impair quality of life, are expensive to treat, and require lengthy healing time, limited attention has been given to device-related PUs. Further work is needed to compare differences in long-term care and acute care populations to document the extent of the problem of device-related PUs, determine population differences (if any), and evaluate the most effective treatment options specific to each setting.…”
Section: Discussionmentioning
confidence: 99%